Raiders And Ruins - Terry Deary
This is another horribly hilarious story from the creators of "Horrible Histories". Eric is a young novice monk in the abbey at Lindisfarne. When he faces a lashing from fearsome Father Patrick, Eric flees in a small boat and is captured in a storm by Norse men. When he befriends Hilda, a young English slave girl, they plan their escape. But the youngsters uncover a secret plan to raid English monasteries and find themselves part of the raiding party on Lindisfarne itself. Can they save Eric's beloved monastery, its treasures and habitants?